2001
DOI: 10.1046/j.1523-1739.2001.015003710.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest Poaching in Neotropical Parrots

Abstract: Although the poaching of nestlings for the pet trade is thought to contribute to the decline of many species of parrots, its effects have been poorly demonstrated. We calculated rates of mortality due to nest poaching in 23 studies of Neotropical parrots, representing 4024 nesting attempts in 21 species and 14 countries. We also examined how poaching rates vary with geographic region, presence of active protection programs, conservation status and economic value of a species, and passage of the U.S. Wild Bird … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
130
1
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 27 publications
4
130
1
12
Order By: Relevance
“…High rates of nesting success for Thick-billed Parrots have also been attributed in part to low rates of poaching (1 of 187 nests) (Monterrubio et al 2002). Many studies reporting low reproductive output for parrots were conducted in areas where poaching affects productivity and nesting success (Martuscelli 1995;Wright et al 2001;Rodríguez Castillo and Eberhard 2006;Sanz and Rodríguez Ferraro 2006). However for some species, low productivity can be explained not by the influence of poaching but by high levels of predation and low food availability (Renton and Salinas Melgoza 2004).…”
Section: Factors Potentially Influencing Reproductive Outputmentioning
confidence: 99%
“…High rates of nesting success for Thick-billed Parrots have also been attributed in part to low rates of poaching (1 of 187 nests) (Monterrubio et al 2002). Many studies reporting low reproductive output for parrots were conducted in areas where poaching affects productivity and nesting success (Martuscelli 1995;Wright et al 2001;Rodríguez Castillo and Eberhard 2006;Sanz and Rodríguez Ferraro 2006). However for some species, low productivity can be explained not by the influence of poaching but by high levels of predation and low food availability (Renton and Salinas Melgoza 2004).…”
Section: Factors Potentially Influencing Reproductive Outputmentioning
confidence: 99%
“…Wright et al [69] suggested that the average nest poaching rate in neotropical parrots is 30%, while Gonzales [70] documented harvesting quotas of 61.1%…”
Section: Anthropogenic Simulationsmentioning
confidence: 99%
“…Es de anotar que la mayor parte de los individuos que ingresan al centro se encuentran en estado juvenil o neonatos, extraídos de sus nidadas. Dicha extracción de nidos es un factor de mortalidad de psitácidos generalizado y biológicamente significativo (15). Para México, se conoce que la cadena captura, transporte, distribución y venta, genera mortalidades estimadas del 77% de los individuos antes de poder ser entregados al consumidor, dado al trato inhumano que se le da a los individuos (16).…”
Section: Discussionunclassified